Regulation of Candida albicans Hyphal Morphogenesis by Endogenous Signals - Kornitzer, Daniel (J Fungi (Basel), 2019)
Candida albicans is a human commensal fungus that is able to assume several morphologies, including yeast, hyphal, and pseudohyphal. Under a range of conditions, C. albicans performs a regulated switch to the filamentous morphology, characterized by the emergence of a germ tube from the yeast cell, followed by a mold-like growth of branching hyphae. This transition from yeast to hyphal growth has attracted particular attention, as it has been linked to the virulence of C. albicans as an opportunistic human pathogen. Signal transduction pathways that mediate the induction of the hyphal transcription program upon the imposition of external stimuli have been extensively investigated. However, the hyphal morphogenesis transcription program can also be induced by internal cellular signals, such as inhibition of cell cycle progression, and conversely, the inhibition of hyphal extension can repress hyphal-specific gene expression, suggesting that endogenous cellular signals are able to modulate hyphal gene expression as well. Here we review recent developments in the regulation of the hyphal morphogenesis of C. albicans, with emphasis on endogenous morphogenetic signals.